Management in the Use of Structural and Cohesion Funds and the Absorption of European Funds in Romania - LUPĂNCESCU, Mihaela (Journal of Advanced Research in Management; Vol 8 No 2 (2017): JARM Volume VIII Issue 2(16) Winter 2017DO - 10.14505//jarm. v8.2(16).03, 2018)
One of the reasons for Romania's choice for EU integration is the desire to develop economically and socially. Each country seeks to provide the best possible standard of living for its citizens, good living conditions, as accessible and quality education as possible, adequate health care options, these goals being reflected in the option to be part of a formation economic development with a higher level of development and stability than the Eupean Union. Romania has witnessed remarkable macroeconomic performance in recent years, even in the context of still feeling the effects of the international financial crisis in the global economy.